The Laity and the Liturgical Homily. Beyond Theological and Canonical Restrictions to a New Theological Framework for Participation - Daly, Shane Thomas (Trinity College Dublin. School of Religion. Discipline of Religions and Theology, 2025)
Can laypeople preach liturgical homilies? This is the question this thesis sets out to explore in light of the present canonical and theological norms that restrict the practice. A review of the theology of preaching through the lens of Karl Barth, and the recovery of the liturgical homily by the Catholic tradition at the time of the Second Vatican Council, reveals the importance of reviewing, analysing and assessing the present restriction on practice. Four presuppositions are foundational to the official ecclesiastical position and underpin the canonical restrictions: 1) the traditional identification of preaching with holy orders; 2) concerns that regular lay liturgical preaching blurs the distinction between the hierarchical and common priesthoods; 3) an emphasis on the laity’s secularity; and 4) ordination as empowering the priest or deacon to act in the person of Christ the Head. These presuppositions are analysed to determine whether or not they remain valid as a basis for excluding lay liturgical preaching. The reservation of the liturgical homilies to deacons receives particular attention. The role assigned to the deacon in post-conciliar pastoral and liturgical life is contrasted with how lay ministry is conceived, developed, and restricted during the same period. Rather than develop ministry by laity, ecclesiastical authorities built up the role and importance of the deacon in response to the decline in the number of clergy. The impact and implication of Benedict XVI’s 2009 clarification that deacons neither act in the person of Christ the Head nor were a part of the ministerial priesthood is explored by arguing that this change in the deacon’s status means they minister on the same basis as laity, namely, on the basis of their baptismal priesthood. Having identified theological inconsistences with the presuppositions that inform much of the official theological and canonical positions, an alternative set of presuppositions and criteria are proposed as the basis for establishing an installed permanent ministry of liturgical preaching. These criteria are baptism as a consecration for mission, call, charism, discernment by community, formation, and installation by ritual. These criteria are built upon two presuppositions, namely ministry as a participation in the divinely instituted priesthood of the bishop and the authority of the Church to reorder the sacrament of order to meet pastoral needs.
APPROVED